Direct writing of silver nanowire-based ink for flexible transparent capacitive touch pad. (22nd October 2019) - Nair, Nitheesh M; Daniel, Kevin; Vadali, Sai Chandrahaas; Ray, Debdutta; Swaminathan, P
Abstract: Printed electronics is an emerging field involving the fabrication of electronic devices by the patterned deposition of material inks. For many systems, producing stable printable inks is the key challenge. In this work, the formulation of a silver nanowire-based ink for printed transparent electrode applications is described. The nanowire length and rheology of the ink are adjusted for printing, with a single layer printed film having a sheet resistance of approximately 30 Ω/□ and a transmittance of 94% at 550 nm. The number of printed layers and volume per layer are optimized to get maximum transparency with good electrical conduction. A transparent capacitive touch pad, in the form of a 2 × 2 matrix is implemented, using this ink and with PDMS as the dielectric. The touch pad has a high degree of flexibility with a resistance variation less than 2% after 10 000 bending cycles. The formulated nanowire ink can be extended for other flexible and stretchable transparent sensing applications.